2019
DOI: 10.1002/vms3.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunosuppressive drugs on cytokine production in canine whole blood stimulated with lipopolysaccharide or a combination of ionomycin and phorbol 12‐myristate 13‐acetate

Abstract: A pharmacodynamic assay has been previously developed to monitor ciclosporin treatment in dogs by assessing inhibition of cytokine transcription after whole blood stimulation with 12‐myristate 13‐1 acetate and ionomycin ( PMA /I). In this study, whole blood stimulation with either PMA /I or lipopolysaccharide ( LPS ) was used to assess the effect of multiple drugs (azathioprine, ciclosporin, mycophenolate, leflunomide and prednisone) after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…This may be a consequence of more frequent infections in these patients. Furthermore, post‐transplantation, we found that a decreased percentage of circulating MAIT cells was producing TNFα, potentially due to the use of immunosuppressive agents [59]. Nevertheless, in the current study, there was no evidence to suggest that a decreased number or the impaired function of circulating MAIT cells are responsible for the frequent infections observed in RTRs both before and after transplantation.…”
Section: Discussioncontrasting
confidence: 57%
“…This may be a consequence of more frequent infections in these patients. Furthermore, post‐transplantation, we found that a decreased percentage of circulating MAIT cells was producing TNFα, potentially due to the use of immunosuppressive agents [59]. Nevertheless, in the current study, there was no evidence to suggest that a decreased number or the impaired function of circulating MAIT cells are responsible for the frequent infections observed in RTRs both before and after transplantation.…”
Section: Discussioncontrasting
confidence: 57%
“…In plasma from whole-blood stimulation, however, LPS induced a much higher concentration of TNF-α, and PMA/ionomycin-stimulated samples showed low to no detectable TNF-α (Figure 2D). Dandrieux et al (2019) observed similar results after stimulation of canine whole blood with lower TNF-α concentrations in response to PMA/ionomycin compared with LPS stimulation. The discrepancy between the response to PMA/ionomycin in PBMC and in whole blood can be associated with the difference in cell composition in the 2 samples.…”
Section: Development Of Monoclonal Antibodies For Quantification Of Bovine Tumor Necrosis Factor-αsupporting
confidence: 62%
“…Significant changes in cytokine expression were also shown in dogs, especially for TNF α, treated with either high doses of ciclosporin or a standard immunosuppressive dosage of prednisolone. TNF α concentrations significantly decreased [ 104 ]. This effect was also described in a canine endotoxemia model.…”
Section: Resultsmentioning
confidence: 99%